THE EFFECT OF MACROECONOMIC VARIABLES ON FISCAL SUSTAINABILITY IN INDONESIA, PERIOD 2004Q1-2018Q4 - Muhammad Latif Abdullah; FNU Sunaryati (Universitas Airlangga, 2018)
Abstract Fiscal sustainability illustrates the condition of a healthy government budget which can finance government spending without increasing debt supply. The purpose of this study is to analyze the impact of macroeconomic variables on fiscal sustainability which in this study fiscal sustainability is proxied as a government budget deficit. The data used in this study is the 2004Q1-2018Q4 time series data using the Vector Error Correction Model (VECM). The results showed that fiscal conditions in Indonesia are sustainable and macroeconomic variables such as domestic debt andinflation has a positive effect on increasing the government budget deficit. Whereas the variable state revenues and foreign debt negatively affect the government budget deficit.Keywords : Fiscal Sustainability, Government Budget Deficit, Domestic Debt, Foreign Debt.